A scary scene in a scary movie - Blackstone, Matt. (New York : Farrar Straus Giroux, 2011)
Rene, a high school freshman with obsessive-compulsive disorder, finds life to be like a scary movie, and even after he makes friends with the ultra-cool Giovanni he still feels responsible for saving his favorite teacher, dealing with his missing father, courting the beautiful Ariel, and trying to pretend to be normal for the school psychologist.
Publisher's Weekly
Publisher's Weekly, June 2011
Young Adult.
Young Adult
Keywords: Dysfunctional families -- Juvenile fiction; Emotional problems of teenagers -- Juvenile fiction; High schools -- Juvenile fiction; Obsessive-compulsive disorder -- Juvenile fiction; Schools -- Juvenile fiction; Emotional problems -- Fiction; Family problems -- Fiction; High schools -- Fiction; Obsessive-compulsive disorder -- Fiction; Schools -- Fiction; Emotionally disturbed children -- Fiction; Family problems -- Fiction; High schools -- Fiction; Obsessive-compulsive disorder -- Fiction; School stories; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction